Easternisation and Enlightenment. Larry Wolff, Marquis de Ségur and the Younger Europe - Junkiert, Maciej (Poznańskie Studia Slawistyczne, 2022)
The article describes two accounts of Poland and the culture of its people. The first of these dates from 1784 and was written by the Marquis de Ségur, a French diplomat travelling to St Petersburg. The second, from 1840, was written by the Polish poet Adam Mickiewicz, at the time working as a professor at the Collège de France in Paris. I try to show the most important differences between the Enlightenment and Romantic images of Poland. An important context is provided by Larry Wolff’s monograph, which 30 years ago initiated a new phase in research on the European invention of Eastern Europe.